2021
DOI: 10.1590/0001-3765202120210865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant, cytotoxic, antibacterial effects and mineral levels of Verbascum lasianthum Boiss. ex Bentham

Abstract: The present study aimed to determine the antibacterial, antioxidant, cytotoxic activities and element levels of Verbascum lasianthum Boiss. ex Bentham. The free radical scavenging activity, total phenolic content, total antioxidant capacity, total oxidant capacity levels were analyzed as the antioxidant parameters. Seven bacteria and one yeast strains were used to determine the antimicrobial activity. The cytotoxic effects of plant extracts were determined using A549, MCF-7, HepG2 and SH-SY5Y cell lines. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…mutense against SK-MEL cells ( Tatli and Akdemir, 2006b ), V. sinaiticum against Hep-2 and MCF-7 cells. ( Talib and Mahasneh, 2010 ), V. thapsus against A549 cells ( Zhao et al, 2011 ) , V. ovalifolium against SK-MEL-2 cell ( Luca et al, 2019 ), V. nigrum against A431 cells ( Iliescu et al, 2020 ), V. alceoides against HeLa and HUVEC cells ( Dinani et al, 2020 ), and V. lasianthum against A549 cells ( Hazman et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…mutense against SK-MEL cells ( Tatli and Akdemir, 2006b ), V. sinaiticum against Hep-2 and MCF-7 cells. ( Talib and Mahasneh, 2010 ), V. thapsus against A549 cells ( Zhao et al, 2011 ) , V. ovalifolium against SK-MEL-2 cell ( Luca et al, 2019 ), V. nigrum against A431 cells ( Iliescu et al, 2020 ), V. alceoides against HeLa and HUVEC cells ( Dinani et al, 2020 ), and V. lasianthum against A549 cells ( Hazman et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…lasianthum Boiss. ex Bentham, was investigated for its biological activity and element content by [ 15 ]. The study revealed that different concentrations of V .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [12,13,15,17,19,45,46] conducted in various countries have reported a significant success rate in antibacterial activity tests, aligned with the ethnomedicinal background. A synthesis of findings from various studies reveals a consistent pattern of antibacterial efficacy across a diverse range of plants, despite differences in phytochemical composition and geographical origins.…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations